2006
DOI: 10.1063/1.2354425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BaTiO3 on dielectric behavior of BaTiO3–Ni–polymethyl methacrylate composites

Abstract: Effects of ferroelectric BaTiO3 particles were investigated on the dielectric behavior of BaTiO3–Ni–polymethyl methacrylate composites fabricated by a two-step mixing and hot-molding method. The percolation power law in the smearing region was employed to explain the experimental results. The composites exhibit the dependence of the dielectric constant, dielectric loss, and percolation threshold on the concentration and particle size of BaTiO3. The results suggest that BaTiO3 particles play an important role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…To achieve various performance objectives, high-dielectric-constant ferroelectric ceramics such as Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT) [5], Pb(Zr,Ti)O 3 (PZT) [6], LTNO [7], CaCu 3 Ti 4 O 12 (CCT) [8] and BaTiO 3 (BT) [9] have been used as fillers in polymers by previous researchers. Similarly, metallic fillers have also been used to achieve ultrahigh dielectric constants in metal-polymer composites or three-phase composite systems [10][11][12]. The high dielectric constant of the ceramic allowed for a high dielectric constant and a strong piezoelectric effect in the composite for moderate volume fractions of the ceramic filler.…”
Section: Introductionmentioning
confidence: 98%
“…To achieve various performance objectives, high-dielectric-constant ferroelectric ceramics such as Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT) [5], Pb(Zr,Ti)O 3 (PZT) [6], LTNO [7], CaCu 3 Ti 4 O 12 (CCT) [8] and BaTiO 3 (BT) [9] have been used as fillers in polymers by previous researchers. Similarly, metallic fillers have also been used to achieve ultrahigh dielectric constants in metal-polymer composites or three-phase composite systems [10][11][12]. The high dielectric constant of the ceramic allowed for a high dielectric constant and a strong piezoelectric effect in the composite for moderate volume fractions of the ceramic filler.…”
Section: Introductionmentioning
confidence: 98%
“…As the volume fraction of LSCO increased, the cluster of LSCO merged, and there was a continuous path of the adjacent site across the system. Generally, all percolative composites have a small smearing region [3][4][5][6][7][8][9][10][11][12] (V c À V % 0.03, where V and V c are the volume fractions of the conducting filler below and at percolation, respectively). However, as shown in Figure 2, the relative permittivity increased from 183 to 11,713 with an increase of the volume fraction of LSCO from 0.23 to 0.50 in this three-phase composite.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, all ceramic-metal and polymer-metal composites have very narrow smearing regions. [3][4][5][6][7][9][10][11][12] It was reported that the addition of ceramic to polymer-metal composites isolates the metal particles from the clusters, which results in the expansion of the smearing region. 22 As a result, more metal particles can be incorporated into the composites.…”
Section: à4mentioning
confidence: 99%
See 2 more Smart Citations